Method for Detecting Electrical Interface in Sea Area Based on Active Electric Field. Issue 1 (1st January 2023) - Chen, Cong; Wu, Xu; Yang, Jingxuan; Sun, Jiaqing
Abstract: To obtain the direction and distance of the electrical interface in the sea, the active electric field of the electric dipole and two three-component electric field intensity sensors are used to detect them. First, the structure design of the active electric field detection device is given, and then a method for active electric field detection of the electrical interface in the sea area is proposed, that is, the effect of the electrical interface on the active electric field is equivalent to the effect of the mirror electric dipole, locating the position of the mirror dipole can be done by measuring the change of the field strength, and then the interface parameters can be determined according to the symmetrical relationship between the position of the mirror dipole and the source dipole. Both simulation analysis and laboratory test results show that the interface detection method is feasible. The related research provides new ideas for target detection in the sea.